Enkele aspekte van die minerale voeding van Acacia saligna (Labill.) Wendl - Botha, M. J. T.(Marthinus Johannes Theunis) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M.Sc.) -- Universiteit van Stellenbosch, 1979.